2018
DOI: 10.30543/7-2(2018)-6
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Quality Management in Sports Club in Dubai

Abstract: The quality management of the sports clubs is a decisive factor for the development of the organizations, therefore, it is essential to know their dimensions of being able to analyse it, knowing their parts and improving the efficiency and accuracy of the service. The aim is to carry out a diagnosis of the level of implementation of quality in the Sports Clubs of Dubai, UAE. The study questionnaire inspired by the European Foundation for Quality Management is divided into three parts, of which, each consists o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 9 publications
0
1
0
Order By: Relevance
“…The five of them: Leadership, Human Resources, Strategy and Policy, Suppliers / Sponsors / Resources, and Procedures are the set of enablers, while the other four: People outcomes, Customer outcomes, Results for the Society and Key performance results, are the set of the results (E.F.Q.M., 2019; 2021). Alanasari, Sallaoui, and Souissi (2018) evaluated the quality management in a sports club in Dubai by using the EFQM Excellence Model framework. Their results showed that the management was supporting and encouraging programs for promoting quality concepts and applications.…”
Section: Introductionmentioning
confidence: 99%
“…The five of them: Leadership, Human Resources, Strategy and Policy, Suppliers / Sponsors / Resources, and Procedures are the set of enablers, while the other four: People outcomes, Customer outcomes, Results for the Society and Key performance results, are the set of the results (E.F.Q.M., 2019; 2021). Alanasari, Sallaoui, and Souissi (2018) evaluated the quality management in a sports club in Dubai by using the EFQM Excellence Model framework. Their results showed that the management was supporting and encouraging programs for promoting quality concepts and applications.…”
Section: Introductionmentioning
confidence: 99%